The interplay between Helicobacter pylori and gastrointestinal microbiota. (1st January 2021) - Chen, Chieh-Chang; Liou, Jyh-Ming; Lee, Yi-Chia; Hong, Tzu-Chan; El-Omar, Emad M; Wu, Ming-Shiang
ABSTRACT: The complex population of microbes in the human gastrointestinal (GI) tract interacts with itself and with the host, exerting a deep influence on health and disease development. The development of modern sequencing technology has enabled us to gain insight into GI microbes. Helicobacter pylori colonization significantly affects the gastric microenvironment, which in turn affects gastric microbiota and may be correlated with colonic microbiota changes. Crosstalk between H. pylori and GI commensal flora may play a role in H. pylori –related carcinogenicity and extragastric manifestations. We review current knowledge on how H. pylori shapes GI microbiota with a specific focus on its impact on the stomach and colon. We also review current evidence on colonic microbiota changes attributed to eradication therapy based on the clinical studies performed to date.